Diagnostic Accuracy of Chest Ultrasonography in Diagnosing Pneumothorax Taking CT Chest as A Gold Standard: Diagnostic Accuracy of Chest Ultrasonography in Diagnosing Pneumothorax - Nazir, Muhammad Hassan; Khan, Nasir; Kashmir, Saba Binte; Raja, Riffat; Zahoor, Anam; Nadeem, Beenish (Pakistan Journal of Health Sciences, 2025)
Ultrasound of the lung is an emerging diagnostic technique for diagnosing pneumothorax in patients with traumatic injury which is faster, safer, or more accessible than a conventional computed tomography scan. Objectives: To assess the diagnostic accuracy of chest ultrasonography in diagnosing pneumothorax using computed tomography chest as a gold standard. Methods: A cross-sectional validation study was conducted at the Radiology Department of Holy Family Hospital, from Nov 2022 to May 2023. Adult patients of either gender, with clinical suspicion of pneumothorax either traumatic or spontaneous, were included. Patients undergone chest ultrasound and pneumothorax were confirmed by the presence of sonographic features. Plain computed tomography chest imaging was done to confirm the diagnosis and compare it with ultrasound results. Results: There were ninety patients included. The ultrasound technique was found to have 92.8% sensitivity and 91.7% specificity to correctly diagnose pneumothorax as compared to chest computed tomography. The positive and negative predictive values were found to be 94.5% and 88.5% respectively, and overall diagnostic power was 92.2%. Conclusions: It was concluded that the diagnostic accuracy of chest ultrasonography in detecting pneumothorax is comparable to computed tomography Chest gold standard and this technique can be utilized in emergency care settings.